Study of a FWH-based permeable-surface formulation for propeller hydroacoustics. (15th November 2021) - Testa, C.; Porcacchia, F.; Zaghi, S.; Gennaretti, M.
Abstract: This paper investigates the use of the permeable surface integral formulation based on the Ffowcs Williams–Hawkings Equation to predict the noise field generated by marine propellers. After derivation of the integral formulation, first, in the framework of potential flows, its main features are discussed for case-studies that allow a straightforward interpretation of the results achieved. Then, issues related to the use of pseudo-compressible, performance-oriented CFD solvers to detect the sources of sound over the permeable surface of integration are carefully examined. Among them, the occurrence of undesired boundary reflection effects and the strategies for their mitigation are discussed. The end-cap problem, open v s closed surface strategies, placement/sizing of the permeable surface and CFD grid topology suitability for hydroacoustic purposes are further topics considered in the paper. In order to provide guidelines and best practices for FWH permeable-surface hydroacoustics, the strategic choices made in determining the numerical predictions are discussed in detail. As one of the most interesting outcomes of the numerical investigation, it has been proven that accurate noise predictions are achievable through tailored CFD grid stretching capable of avoiding boundary reflections, an issue affecting hydroacoustics more than hydrodynamics. Highlights: FWH permeable-surface based predictions need accurate hydrodynamic dataset. Boundary reflections from CFD-pseudocompressible data negatively affect noise results. Permeable-surface acoustic formulations may generate spurious noise. Open/closed permeable surfaces yield different approximations of propeller noise. Acoustic signal distortion arises from vortex structures cut by the porous surface.